北极地区大地构造特征及其构造演化——北极地区大地构造编图研究进展 - 李江海; 刘仲兰; 王洛; 张华添 (海洋学报（中文版）, 2016)
北极地区具有丰富的油气资源,但是受极度寒冷气候和广泛分布冰盖的影响,北极是全球地质研究程度最低的地区之一.为此,基于最新地球物理数据,结合文献资料中的地貌、地质、矿产资源资料,编制了北极地区大地构造图(1∶500万).通过系统的编图研究,认为北极地区位于泛大陆腹地,中生代以来的构造演化受到冰岛地幔柱的垂向作用和欧亚-劳伦板块缓慢的顺时针旋转的水平作用共同制约.其构造演化可归纳为3个阶段:(1)早中生代:北亚-北美西北部(远东-科迪勒拉)造山带俯冲-造山增生阶段,古太平洋向北俯冲,古亚洲洋最终关闭,泛大陆最终形成;(2)侏罗纪-白垩纪:伴随着加拿大盆地张开,南阿纽伊洋盆俯冲消亡并形成南阿纽伊缝合带,两者之间在运动学上具有耦合联系,并伴随其间转换断层的调节作用;(3)新生代以来北大西洋中脊持续扩展传播,造成欧亚盆地张开和加科尔洋中脊发育.北极地区处于全球不同构造域之间的桥梁和枢纽.随着北冰洋洋盆伸展作用发展及加科尔洋中脊向南传播,它将西南贯通北太平洋构造域(远东造山带),彻底改变全球中生代以来的构造格局. The Arctic is rich in hydrocarbon resources,but its level of geological research is almost lowest in the world due to harsh natural climatic conditions and complicated tectonic evolution.Herein,the tectonic map of the Arctic (1 ∶ 5 000 000) was compiled based on newly updated geophysical data,and combination of geology,geomorphology,and resource data.From compiling of the tectonic map,this paper recognized the tectonic evolution of Arctic to be influenced by the vertical effect of Iceland Mantle Plume,and the horizontal effect of clockwise rotation of Eurasia-Laurentia supercontinent.The tectonic evolution of Arctic Ocean is divided into three stages:(1) Early Mesozoic.Paleo-Pacific Ocean subducted northwards.Paleo-Asian Ocean closed,leading to the formation of supercontinent.(2) Jurassic-Cretaceous.South Anui Suture was formed,accompanied by the coupling of Canada Basin opening and South Anui Ocean closing.This process is accommodated by development of transform faults.(3) Cenozoic.North Mid-Atlantic Ridge extended northwards,leading to the forming of Gakkel Ridge.Arctic Ocean represents the hinge of global tectonic domains.Along with the extension of Gakkel Ridge,it will connect with North Pacific tectonic domain (Far East Orogen),changing the global tectonic pattern since Mesozoic. 国家海洋局国际合作司和中国极地研究中心联合项目——北极圈大地构造编图; 印度洋脊多金属硫化物成矿潜力与资源环境评价; 西南印度洋脊合同区多金属硫化物资源评价 中文核心期刊要目总览(PKU) 中国科技核心期刊(ISTIC) 中国科学引文数据库(CSCD) 7 85-96 38